2022
DOI: 10.3390/nu14204396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-Citrulline Supplementation on Endothelial Function and Blood Pressure in Hypertensive Postmenopausal Women

Abstract: Aging and menopause are associated with decreased nitric oxide bioavailability due to reduced L-arginine (L-ARG) levels contributing to endothelial dysfunction (ED). ED precedes arterial stiffness and hypertension development, a major risk factor for cardiovascular disease. This study investigated the effects of L-citrulline (L-CIT) on endothelial function, aortic stiffness, and resting brachial and aortic blood pressures (BP) in hypertensive postmenopausal women. Twenty-five postmenopausal women were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 79 publications
(106 reference statements)
2
31
0
Order By: Relevance
“…52,53 Oral consumption of watermelon juice has been reported to reduce circulating levels of soluble vascular cell adhesion molecule-1 (sVCAM-1, a biomarker of inflammatory endothelial activation) in obese postmenopausal women, 53 peripheral arterial stiffness in healthy young women, 54 and blood pressure in hypertensive postmenopausal women. 55 Cit and watermelon juice hold promise for improving reproductive health 30 as well as vascular and metabolic health 56,57 in humans.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Oral consumption of watermelon juice has been reported to reduce circulating levels of soluble vascular cell adhesion molecule-1 (sVCAM-1, a biomarker of inflammatory endothelial activation) in obese postmenopausal women, 53 peripheral arterial stiffness in healthy young women, 54 and blood pressure in hypertensive postmenopausal women. 55 Cit and watermelon juice hold promise for improving reproductive health 30 as well as vascular and metabolic health 56,57 in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The AA metabolism is impaired in CKD and elevated ADMA levels are associated with higher vascular stiffness and reduced NO contribution. Several studies have suggested the exogenous supplementation of AAs, e.g., arginine [ 41 ], citrulline [ 42 ] and L- phenylalanine [ 43 ], as a potential therapeutic option to target vascular disease; however current evidence is contradictory and may depend on differences in dose and administration route. In conclusion, we suggest that uremia is associated with alterations in AA metabolism that may affect vascular function in CKD towards an increased risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, evidence indicates that ARG supplementation improves endothelial function in individuals with a baseline brachial FMD lower than 7% [ 39 ], suggesting benefits of ARG and CIT are more prominent in individuals with endothelial dysfunction. Previous literature has elucidated 4 weeks of CIT significantly increased brachial FMD compared to PL in hypertensive postmenopausal women [ 40 ]. Our study demonstrated for the first time that sfemFMD increased after CIT supplementation alone compared to PL.…”
Section: Discussionmentioning
confidence: 99%
“…Oral CIT was an efficient ARG precursor that results in an important increase in systemic ARG availability [ 57 ]. We recently reported that this CIT dose for 4 weeks improved brachial FMD by increasing ARG availability in postmenopausal women with hypertension [ 40 ]. Our findings suggest that 10 g daily of CIT supplementation may help to increase leg LM when combined with SVLIRT, by increasing leg endothelial function via an ARG/NO pathway-induced vasodilation [ 33 , 58 ].…”
Section: Discussionmentioning
confidence: 99%